PENGGUNAAN MEDIA PEMBELAJARAN SEBAGAI UPAYA MENCIPTAKAN PEMBELAJARAN AKTIF DI KELAS - Adya Pribadi, Reksa; Nurhasanah, Ana; Ari Syahrial, Muhammad (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2021)
Learning media is a learning tool or device that can be used by teachers to assist them in conveying learning messages. This study aims to determine how the influence of learning media in creating active learning. This research was conducted using descriptive qualitative method. Data collection techniques in this study used interview and observation techniques. Based on the research that has been done, the implementation of learning at SDN Kebon Jahe, especially in class V, has used learning media that makes learning run active.